Increased right atrial appendage apoptosis is associated with differential regulation of candidate MicroRNAs 1 and 133A in patients who developed atrial fibrillation after cardiac surgery. (August 2018) - Tsoporis, James N.; Fazio, Anastasia; Rizos, Ioannis K.; Izhar, Shehla; Proteau, Gerald; Salpeas, Vasileos; Rigopoulos, Angelos; Sakadakis, Eleftherios; Toumpoulis, Ioannis K.; Parker, Thomas G.
Abstract: Atrial fibrillation (AF) following on-pump coronary artery bypass grafting (CABG) is a common condition associated with increased morbidity and mortality. We investigated the possibility that miRs may play a contributory role in postoperative AF and associated apoptosis. A total of 42 patients (31 males and 11 females, mean age 65.0 ± 1.3 years) with sinus rhythm and without a history of AF were prospectively enrolled. We examined the levels of the muscle-specific miRs 1 and 133A and markers of apoptosis including TUNEL staining, caspase-3 activation, Bcl2 and Bax mRNAs in right atrial appendage (RAA) biopsies and blood plasma taken before aortic cross-clamping and after reperfusion. After reperfusion, indices of apoptosis increased the RAA. There was no change in tissue or plasma miR −1 and -133A levels compared to pre CABG. However, in patients who postoperatively developed AF ( n  = 14, 7 males and 7 females), compared to patients that remained in SR ( n  = 28, 24 males and 4 females) post CABG, tissue miR-1 increased whereas miR-133A decreased and negatively correlated with RAA apoptosis. Mechanistically, overexpression of miR-133A inhibited hypoxia-induced rat neonatal cardiomyocyte apoptosis and phosphorylated pro-survival Akt, responses abolished by a miR-133A antisense inhibitor oligonucleotide or by pre-treatment with an Akt inhibitor. In postoperative AF, differential regulation of pro- and anti-apoptotic miRs-1 and -133A respectively in the RAA, may contribute to postoperative apoptosis. These results provide new insights into molecular mechanisms of postoperative AF with potential therapeutic implications. Highlights: Post-operative atrial fibrillation (POAF) induces right atrial appendage (RAA) apoptosis. POAF, pro-apoptotic miR-1 is upregulated in the RAA. POAF, anti-apoptotic miR-133A is downregulated in the RAA. Plasma miRs -1 and -133A do not change POAF. miR-133A inhibits hypoxic-induced cardiomyocyte apoptosis via Akt signaling.